2019
DOI: 10.5507/fot.2019.004
|View full text |Cite
|
Sign up to set email alerts
|

Mallomonas minuscula sp. nov. (Synurales, Chrysophyceae), a new member in the section Torquatae from Vietnam

Abstract: Mallomonas minuscula sp. nov. is described from Vietnam based on silica-scale morphology studied by means of transmission and scanning electron microscopy. This species belongs to the Mallomonas mangofera complex and is characterized by small scales with large polygonal papillae on the shield, raised wide arms on the anterior submarginal rib with small papillae, and a small "window" in the angle of the posterior submarginal rib. Scales of Mallomonas minuscula were found in nine localities from six provinces of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Mallomonas lamii (Figure 3A), M. loricata (Figure 3B), M. minuscula (Figure 3G), and M. paragrandis (Figure 3J) were recently described in Vietnam and are widespread throughout the country [46,47,55,57,59]. Mallomonas loricata scales were found earlier in Malaysia and Singapore and identified as M. matvienkoae [28].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Mallomonas lamii (Figure 3A), M. loricata (Figure 3B), M. minuscula (Figure 3G), and M. paragrandis (Figure 3J) were recently described in Vietnam and are widespread throughout the country [46,47,55,57,59]. Mallomonas loricata scales were found earlier in Malaysia and Singapore and identified as M. matvienkoae [28].…”
Section: Discussionmentioning
confidence: 96%
“…These studies have revealed a very rich flora from the order Synurales, including 57 taxa from genera Mallomonas and Synura. Indeed, 19 new species from the genus Mallomonas [40,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] and one Synura species [60] were described in these studies. However, the northern part of Vietnam, which differs in hydrology, climate, and anthropogenic impact from the Central and Southern provinces, is lacking sufficient descriptive studies.…”
Section: Introductionmentioning
confidence: 99%
“…Information about diversity of algae from the order Synurales in the Northern Vietnam has also been published recently, including the description of two new species [76][77][78]. In addition, a number of new species for science have been described from individual regions of the country [71,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91]. However, Central Vietnam, except for certain areas of the Khanh Hoa province, has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, they are at present far less reported from low latitude areas, as most of the stomatocysts are reported from temperate and cold zones. During the survey of silica scaled chrysophytes from tropical and subtropical areas, such as southern China (Wei et al 2013(Wei et al , 2014Nĕmcovà et al 2015), Vietnam (Gusev & Martynenko 2022;Gusev et al 2015Gusev et al , 2016Gusev et al , 2017Gusev et al , 2018Gusev et al , 2019Gusev et al , 2020Gusev et al , 2021, Indonesia (Kapustin et al 2019) and Cameroon (Piatek & Lukaszek 2016), more and more new species were reported. It confirmed that mountain lakes and generally water bodies in poorly studied tropical and subtropical areas from East Asia are rich with chrysophytes and many new species can be found there.…”
Section: Discussionmentioning
confidence: 99%